Derivative Security Markets, Market Manipulation, and Option Pricing Theory - Jarrow, Robert A. (Journal of Financial and Quantitative Analysis, 1994)
This paper studies a new theory for pricing options in a large trader economy. This theory necessitates studying the impact that derivative security markets have on market manipu? lation. In an economy with a stock, money market account, and a derivative security, it is shown, by example, that the introduction ofthe derivative security generates market manip? ulation trading strategies that would otherwise not exist. A sufficient condition is provided on the price process such that no additional market manipulation trading strategies are introduced by a derivative security. Options are priced under this condition, where it is shown that the standard binomial option model still applies but with random volatilities.